2015
DOI: 10.4196/kjpp.2015.19.4.327
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Heme Oxygenase-1 in Orexin-A-induced Angiogenesis in Vascular Endothelial Cells

Abstract: The cytoprotective enzyme heme oxygenase-1 (HO-1) influences endothelial cell survival, proliferation, inflammatory response, and angiogenesis in response to various angiogenic stimuli. In this study, we investigate the involvement of HO-1 in the angiogenic activity of orexin-A. We showed that orexin-A stimulates expression and activity of HO-1 in human umbilical vein endothelial cells (HUVECs). Furthermore, we showed that inhibition of HO-1 by tin (Sn) protoporphryin-IX (SnPP) reduced orexin-A-induced angioge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…The existing literature on the role of orexin-A in the regulation of molecules implicated in the atherogenesis process is scarce. Recently, Kim et al found that incubation of HUVECs with orexin-A at concentrations of 0.1-0.3 µM and 0.2 µM, similar to those used in our study, for 2 and 8 h, respectively positively affect the expression and activity of HO-1, which is an anti-inflammatory molecule [11].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The existing literature on the role of orexin-A in the regulation of molecules implicated in the atherogenesis process is scarce. Recently, Kim et al found that incubation of HUVECs with orexin-A at concentrations of 0.1-0.3 µM and 0.2 µM, similar to those used in our study, for 2 and 8 h, respectively positively affect the expression and activity of HO-1, which is an anti-inflammatory molecule [11].…”
Section: Discussionsupporting
confidence: 76%
“…Recently, Kim et al demonstrated that orexin-A induced the expression of heme oxygenase-1 (HO-1) in endothelial cells (HUVECs) [11]. HO-1 is an anti-inflammatory, antioxidant, and cytoprotective enzyme that exerts beneficial effects on vascular damage and mediates the protection of endothelial cells by regulating endothelial cell activation and inhibiting endothelial cellular apoptosis [11].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with vascular disorders, their cerebrospinal fluids have reduced orexin A levels . In endothelial cells, orexin A induces angiogenesis and promotes the neovascularization . The vascular endothelial dysfunction is the early event of atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…The capability of ECFCs to form tubule-like structures was determined using a tube formation assay with modifications of previous procedures [ 11 ]. Twenty-four-well plates were coated with ice-cold Matrigel solution (Phenol Red-Free; BD Biosciences, NJ, USA) and incubated at 37℃ for at least 30 min to allow the Matrigel to solidify.…”
Section: Methodsmentioning
confidence: 99%